Rhetoric in American Anthropology : Gender, Genre, and Science - Applegarth, Risa (Book collections on Project MUSE., 2014)
"In the early twentieth century, the field of anthropology transformed itself from the "welcoming science," uniquely open to women, people of color, and amateurs, into a professional science of culture. The new field grew in rigor and prestige but excluded practitioners and methods that no longer fit a narrow standard of scientific legitimacy. In Rhetoric in American Anthropology, Risa Applegarth traces the "rhetorical archeology" of this transformation in the writings of early women anthropologists"--